Variation and prognostic potential of the gut antibiotic resistome in the FINRISK 2002 cohort - Pärnänen, Katariina; Ruuskanen, Matti O.; Sommeria-Klein, Guilhem; Laitinen, Ville; Kantanen, Pyry; Méric, Guillaume; Gazolla Volpiano, Camila; Inouye, Michael; Knight, Rob; Salomaa, Veikko; Havulinna, Aki S.; Niiranen, Teemu; et al. (NATURE PORTFOLIO, 2025)
The spread of antibiotic-resistant bacteria has severely reduced the efficacy of antibiotics and now contributes to 1 million deaths annually. The gut microbiome is a major reservoir of antibiotic resistance in humans, yet the extent to which gut antibiotic resistance gene load varies within human populations and the drivers that contribute most to this variation remain unclear. Here, we demonstrate, in a representative cohort of 7095 Finnish adults, that socio-demographic factors, lifestyle, and gut microbial community composition shape resistance gene selection and transmission processes. Resistance was linked not only to prior use of antibiotics, as anticipated, but also to frequent consumption of fresh vegetables and poultry, two food groups previously reported to contain antibiotic-resistant bacteria. Interestingly, resistance was not linked to the consumption of high-fat and high-sugar foods, but was consistently higher in females and urban high-income individuals, who currently have generally lower mortality rates. Nevertheless, during the 17-year follow-up, high resistance was associated with a 1.07-fold increase in mortality risk, comparable to elevated blood pressure, and with a heightened risk of sepsis. These findings highlight risks and socio-demographic dimensions of antibiotic resistance that are particularly relevant in the current context of global urbanization and middle-class growth.